At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let's solve the equation step-by-step.
Given:
[tex]\[ 2^{x^2 - 53x + 25} = 32^{2 - 9x} \][/tex]
First, recognize that [tex]\(32\)[/tex] can be written in terms of a base of [tex]\(2\)[/tex] since [tex]\(32 = 2^5\)[/tex]. Thus, the equation can be rewritten:
[tex]\[ 2^{x^2 - 53x + 25} = (2^5)^{2 - 9x} \][/tex]
Next, apply the power of a power rule [tex]\((a^m)^n = a^{mn}\)[/tex]:
[tex]\[ 2^{x^2 - 53x + 25} = 2^{5(2 - 9x)} \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ x^2 - 53x + 25 = 5(2 - 9x) \][/tex]
Expand the right-hand side:
[tex]\[ x^2 - 53x + 25 = 10 - 45x \][/tex]
Move all terms to one side of the equation to set it to zero:
[tex]\[ x^2 - 53x + 25 - 10 + 45x = 0 \][/tex]
Simplify the equation:
[tex]\[ x^2 - 8x + 15 = 0 \][/tex]
This is a quadratic equation. Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a=1\)[/tex], [tex]\(b=-8\)[/tex], and [tex]\(c=15\)[/tex]:
[tex]\[ x = \frac{-(-8) \pm \sqrt{(-8)^2 - 4 \cdot 1 \cdot 15}}{2 \cdot 1} \][/tex]
Calculate the discriminant:
[tex]\[ x = \frac{8 \pm \sqrt{64 - 60}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{4}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm 2}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{8 + 2}{2} = 5 \quad \text{and} \quad x = \frac{8 - 2}{2} = 3 \][/tex]
Thus, the solutions to the equation are:
[tex]\[ \boxed{3 \text{ and } 5} \][/tex]
Given:
[tex]\[ 2^{x^2 - 53x + 25} = 32^{2 - 9x} \][/tex]
First, recognize that [tex]\(32\)[/tex] can be written in terms of a base of [tex]\(2\)[/tex] since [tex]\(32 = 2^5\)[/tex]. Thus, the equation can be rewritten:
[tex]\[ 2^{x^2 - 53x + 25} = (2^5)^{2 - 9x} \][/tex]
Next, apply the power of a power rule [tex]\((a^m)^n = a^{mn}\)[/tex]:
[tex]\[ 2^{x^2 - 53x + 25} = 2^{5(2 - 9x)} \][/tex]
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ x^2 - 53x + 25 = 5(2 - 9x) \][/tex]
Expand the right-hand side:
[tex]\[ x^2 - 53x + 25 = 10 - 45x \][/tex]
Move all terms to one side of the equation to set it to zero:
[tex]\[ x^2 - 53x + 25 - 10 + 45x = 0 \][/tex]
Simplify the equation:
[tex]\[ x^2 - 8x + 15 = 0 \][/tex]
This is a quadratic equation. Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a=1\)[/tex], [tex]\(b=-8\)[/tex], and [tex]\(c=15\)[/tex]:
[tex]\[ x = \frac{-(-8) \pm \sqrt{(-8)^2 - 4 \cdot 1 \cdot 15}}{2 \cdot 1} \][/tex]
Calculate the discriminant:
[tex]\[ x = \frac{8 \pm \sqrt{64 - 60}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm \sqrt{4}}{2} \][/tex]
[tex]\[ x = \frac{8 \pm 2}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{8 + 2}{2} = 5 \quad \text{and} \quad x = \frac{8 - 2}{2} = 3 \][/tex]
Thus, the solutions to the equation are:
[tex]\[ \boxed{3 \text{ and } 5} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.